Potret Layanan Antenatal Care (ANC) Di Wilayah Pasca Bencana Gempa Cianjur - Lisa Dwi Astuti; Nor Tri Astuti Wahyuningsih (STIKES Ngesti Waluyo, 2026)
The earthquake that struck Cianjur Regency resulted in damage to public and healthcare facilities. This emergency directly impacted Antenatal Care (ANC) services for pregnant women, who represent a highly vulnerable group. A decline in post-disaster ANC visits poses a critical risk of increasing pregnancy complications and maternal mortality. This study aims to delineate the implementation of ANC services for pregnant women in the post-earthquake region of Cianjur, utilizing the 10T ANC standard. This study used a descriptive quantitative method. Respondents were pregnant women who had undergone ANC examinations and were selected through purposive sampling. The results indicated that 58.5% of the pregnant women were in their third trimester, 78% were aged 20–35 years, 58.8% had a primary school education background, and 100% were unemployed (housewives). The distance to the ANC examination facilities was short (70.7%), and the facilities were easily accessible (95.1%). Although the 10T ANC examination standards had been implemented, two components demonstrated low coverage: Tetanus Toxoid (TT) immunization screening and laboratory examinations. In conclusion, cross-sectoral collaboration involving the central government, local governments, physicians, healthcare professionals, and the community is imperative to optimize ANC examination services in post-disaster settings. The Minimum Initial Service Package (MISP) must be deployed immediately during health crises. Pregnant women are among the most vulnerable groups severely affected by disasters, facing heightened risks of complications during pregnancy and childbirth, as well as the potential of spontaneous delivery during the chaotic aftermath of a disaster